Estimation of total methane emission from enteric fermentation of ruminant livestock in Bangladesh - Hoque, SA Masudul; Islam, Md Mazharul; Md Selim, Abu Sadeque; Ahmed, Shabbir; Rahman, Md Morshedur (Asian Journal of Medical and Biological Research, 2017)
Ruminant livestock is one of the key elementsfor the agriculture-based economy of Bangladesh, although these animals are often condemned as a source greenhouse gas especially methane (CH4).Total methane emission from the enteric fermentation of ruminants in Bangladesh considering Gazipur, Tangail and Mymensingh district is reflected in the output of the present study. The emission was measured using the dry matter intake (DMI) approach based on the total population of ruminants. Feed intake was recorded from on-farm observation and/or farmers records. It was observed that the ration supplied to bovines consisted of 50-60% green roughage, 31-41% rice straw, and 4-10% concentrate mixture. In terms of DMI rice straw has been contributed the highest (51-65%) proportions followed by green forage (24-31%) and concentrate mixture (7-17%). In small ruminant ration, 90-95% feed (DMI 75-86%) was supplied from green grasses and remaining from concentrate mixtures. Although buffalo individually irrespective of sex and age emitted highest amount of methane followed crossbred and indigenous cattle, goat and sheep, the males produced a higher amount of methane than those of female in all species. Total methane emission in Gazipur, Tangail, and Mymensingh districts were 13359.15, 13250.65 and 13653.75 Kg/day and 4876.11, 4836.50 and 4983.62 000?Kg/year, respectively. In total 848,320 Kg/day and 309,630 000Kg/year methane was measured to be emitted in Bangladesh by 56.33 million ruminant livestock where 64.79% had come from indigenous cattle followed by crossbreed cattle (20.82%), Goat (8.79%), Buffalo (5.17%) and sheep (0.43%). Asian J. Med. Biol. Res. June 2017, 3(2): 245-253